Effect of nitrogen fertilisation on the phytic acid, mineral and trace element contents of oats - Eurola, Merja; Kontturi, Markku; Tuuri, Hannu (MTT, 2004)
The purpose of the study was to obtain information on the effects of different cultivation practises on the uptake and formation of some chemical components in oats. The effect of nitrogen fertilisation on the phytic acid, mineral and trace element contents of oats were studied during 1997-1999 at 2 locations in Finland. Phytic acid has considered to have an unfavourable effect on the bioavailability of nutrients as it can form complexes with cationic elements. The nitrogen fertilisation trials employed 5 N rates (0, 40, 80, 120 and 160 kg N ha-1) with four cultivars (Aarre, Katri, Kolbu and Salo). Mineral and trace element contents were determined after wet digestion by inductively coupled plasma emission spectrometry (ICP-AES). Phytic acid was determined after extraction and ferric precipitation procedure using ICP-AES to determine phosphorus (Plaami & Kumpulainen 1991). The nitrogen fertilisation increased significantly the Cu, Zn and Fe contents of oats at the higher 120 and 160 kg N ha-1 (p < 0.001) levels. This may be due to the acidification and increased ionic strenghts that can enhance the solubility or desorption of trace elements. Slight increment was also observed in the phytic acid content in dry and warm growing seasons 1997 and 1999, whereas an opposite trend was observed in cold and wet growing season 1998. Mean phytic acid content of oats in the trials was 13.3 mg/g dry weight. Ca, Mg and P contents were not affected; K and Mn contens were slightly decreased at high nitrogen application rates (p ?___ 0.01). Clear cultivar differences were also detected. Plaami, S. & Kumpulainen, J. 1991. J. Agric. Food Chem. 51: 2608-2614.
Keywords: Ka; kivennäiset ja hivenaineet; kaura; Avena sativa; typpilannoitus; fytiinihappo; lajike; oat; Avena sativa; nitrogen fertilization; phytic acid; mineral and trace elements; cultivar